Design and fabrication of multi-band SRR sensors using 3D printing for liquid characterization - Yahaya, Irfan; Adam, Ahmad Nurhelmy; Abu Bakar, Ahmad Adnan; Abdullah, Shahino Mah; Tamchek, Nizam; Alforidi, Ahmad F.; Alahmadi, Ahmed; Mohd Ghazali, Mohd Ifwat (Elsevier B.V., 2025)
A microstrip line split ring resonator (SRR) sensor is introduced for liquid profiling. The sensor features a microstrip transmission line with two identical SRRs, detecting differential permittivity by loading liquid samples onto the SRRs.3D-printing stereolithography technology with high temperature resin is used to build the sensors. The printed sensor undergoes metallization process by depositing titanium and copper layer, followed by copper electroplating. Different Ti Cu sputtering time was studied to determine optimum parameters for sensor application. It only necessitates a minimal sample volume for detection as any changes in the sample loading induces a change in the resonance frequency of the SRR. The sensors exhibited strong performance, distinguishing between chemicals like methanol, IPA, and silicone oil based on resonance frequency shifts, with the 3.5 GHz sensor achieving the highest sensitivity (1.09 %). The utilization of additive manufacturing for producing 3D-printed sensors could meet the demand for quick and cost-effective microwave sensors.